Employee Training and Firm Performance: Quasi-experimental evidence from the European Social Fund - Pedro S. Martins (Global Labor Organization (GLO), 2020)
As work changes, firm-provided training may become more relevant for good economic and social outcomes. However, so far there is little or no causal evidence about the effects of training on firms. This paper studies a large training grants programme in Portugal, contrasting successful firms that received the grants and unsuccessful firms that did not. Combining several rich data sets, we compare a large number of potential outcomes of these firms, while following them over long periods of time before and after the grant decision. Our difference-in-differences models estimate significant positive effects on take up (training hours and expenditure), with limited deadweight; and that such additional training led to increased sales, value added, employment, productivity, and exports. These effects tend to be of at least 5% and, in some cases, 10% or more.
Keywords: J24; H43; M53; 330; Training subsidies; Productivity; Counterfactual evaluation